Genetics and Epigenetics of Glioblastoma: Applications and Overall Incidence of IDH1 Mutation - Liu, Aizhen; Hou, Chunfeng; Chen, Hongfang; Zong, Xuan; Zong, Peijun (Frontiers in Oncology, 2016)
Glioblastoma is the most fatal brain cancer found in humans. Patients suffering from glioblastoma have a dismal prognosis, with a median survival of 15 months. The tumor may develop rapidly de novo in older patients or through progression from anaplastic astrocytomas in younger patients if glioblastoma is primary or secondary, respectively. During the past decade, significant advances have been made in the understanding of processes leading to glioblastoma, and several important genetic defects that appear to be important for the development and progression of this tumor have been identified. Particularly, the discovery of recurrent mutations in the isocitrate dehydrogenase 1 (IDH1) gene has shed new light on the molecular landscape in glioblastoma. Indeed, emerging research on the consequences of mutant IDH1 protein expression suggests that its neomorphic enzymatic activity catalyzing the production of the oncometabolite 2-hydroxyglutarate influences a range of cellular programs that affect the epigenome and contribute to glioblastoma development. One of the exciting observations is the presence of IDH1 mutation in the vast majority of secondary glioblastoma, while it is almost absent in primary glioblastoma. Growing data indicate that this particular mutation has clinical and prognostic importance and will become a critical early distinction in diagnosis of glioblastoma.